Influence of nitrogen, phosphours and potassium on growth and yield of black cumin (Nigella sativa L.) - K N Srinivasappa, A Nataraja, A A Farooqi, B S Sreeramu (Journal of Spices and Aromatic Crops, 2003)
A field experiment was conducted to study the influence of nitrogen, phosphorus and potassium on growth and seed yield of black cumin at Sanjivini Vatika, University of Agricultural Sciences, Bangalore during 2000-2001. The experiment consisted of twenty seven treatment combinations with three levels each of nitrogen (0, 50 and 100 kg ha-1), phosphorus (0, 20 and 40 kg ha-1) and potassium (0. 30 and 60 kg ha-1), and was laid out in factorial randomized block design with three replica tions. The results revealed significant differences in growth and yield parameters among the treatments. Application of nitrogen at 100 kg ha-1 recorded the maximum values for plant spread (427.75 cm2) and number of seeds (57.52) per pod. Significant differences were also observed with the interaction of NPK at 50:40:30 kg ha-1 producing pods of good size (3.84 cm2), higher test weight of 1000 seeds (2.38 g) and seed yield (17.45 q ha-1).